Inequality of the Turan type for trigonometric polynomials and conjugate trigonometric polynomials in L_0 - Adamov, A. N. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We study inequalities of the Turan type for trigonometric polynomials and conjugate trigonometric polynomials in the quasinorm of L_0 and derivatives of any order. We present expressions for constants in these inequalities and obtain double-sided estimates for them.